1979
DOI: 10.1002/path.1711270305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gonadectomy and oestrogen administration on the response of lymph‐node post‐capillary venules to infection with Toxoplasma gondii

Abstract: The effects of gonadectomy and oestrogen administration on the response of lymph-node post-capillary venules to infection with Toxoplasma gondii have been studied in mice. The endothelial cells of the post-capillary venules were significantly higher in the female than in the male controls. Oophorectomy had no significant effect while orchidectomy increased the height of the cells. However, hexoestrol administration resulted in a rise of the height to maximum levels in the female and in the male gonadectomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…There is growing evidence that hormones underlie increased susceptibility of pregnant females to toxoplasmosis. In female mice, E2 exacerbates, whereas gonadectomy reduces, parasite burden and disease pathogenesis (Kittas and Henry, 1979, 1980). High concentrations of P4 also increase susceptibility to T. gondii during pregnancy by suppressing production of IL-12 and IFN-γ (Jones et al, 2008).…”
Section: Pregnancy and Pregnancy-associated Hormones Affect Disease Pmentioning
confidence: 99%
“…There is growing evidence that hormones underlie increased susceptibility of pregnant females to toxoplasmosis. In female mice, E2 exacerbates, whereas gonadectomy reduces, parasite burden and disease pathogenesis (Kittas and Henry, 1979, 1980). High concentrations of P4 also increase susceptibility to T. gondii during pregnancy by suppressing production of IL-12 and IFN-γ (Jones et al, 2008).…”
Section: Pregnancy and Pregnancy-associated Hormones Affect Disease Pmentioning
confidence: 99%
“…There is growing evidence that hormones underlie increased susceptibility of pregnant females to toxoplasmosis. In female mice, estradiol exacerbates, whereas gonadectomy reduces, parasite burden and disease pathogenesis (Kittas and Henry, 1979, 1980). High concentrations of progesterone also increase susceptibility to T. gondii during pregnancy by suppressing production of IL-12 and IFN-γ (Jones et al, 2008).…”
Section: Hormones Affect Host Immune Responses To Microbesmentioning
confidence: 99%
“…In these studies, female mice developed more severe brain inflammation than male mice following infection. Moreover, a direct role for sex hormones was demonstrated in experiments which found that gonadectomy increased resistance, whereas estrogen administration exacerbated disease in mice (68,70). Similarly, simultaneous gonadectomy and estrogen treatment predisposed guinea pigs to increased parasite burdens compared with nontreated control animals (69).…”
Section: Toxoplasma Gondiimentioning
confidence: 99%